Chunking Phrase to Predict Pause Break in Pontianak Malay Language - Putra Negara, Arif Bijaksana; Magdalena, Yulia; Nyoto, Rudy Dwi; Sujaini, Herry (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 3 December 2019, 2019)
Pause break is one of the indicators of speech to be easily understood in the Text-to-Speech System. This research aims to improve the accuracy of pause prediction in Pontianak Malay Language Sentences based on earlier research using a chunking phrase. This research is done as one of the efforts to preserve Pontianak Malay Language in order not to become extinct as a local language. Chunking method uses RegexpParser function in Natural Language Toolkit to crop sentences into phrases based on the Part of Speech type. In this research, the authors have developed a new grammar and pause break rule that is different from the earlier research to increase the accuracy of pause prediction. The data used is 500 Pontianak Malay Language sentences that have been recorded by a Pontianak Malay Language native speaker to get the pause break analysis. The pause consists of a short pause (symbolized as “/1) and a long pause (symbolized as “/2”). The tests were a test of pause break compatibility in one sentence and a test using f-measure, recall, and precision parameters. Based on the tests that have been done, the new grammar rule and pause break rule from this research have a better prediction accuracy than the earlier research with the correct predictive value of sentences increasing by 23% from the earlier rule.